Compensation to Increase Work Productivity of the Employees - Roddy A. Runtuwarouw (AIBPM Publisher, 2019)
This research aims at analyzing the influence of compensation, work satisfaction and work performance toward work productivity of the employee in district officse at Minahasa Selatan Regency. The data were collected from 86 samples which randomly selected from the total population of 125 employees. Survey method is path analysis to analyze data descriptively and inferentially. . The findings show that: (1) there is a positive direct influence of compensation, work satisfaction, and work performance on employees’ work productivity, (2) there is a positive direct influence of compensation and work satisfaction on employees’ work performanc, and (3) there is a positive direct influence of compensation on employees’ job satisfaction. The findings recommend that to improve the quality of employee work productivity, it needs to intensify compensation, job satisfaction and work performance.